A Self-Efficacy Theory-Based Program to Reduce Diabetic Foot Ulcer Risk in Agricultural Areas - Ana Nistiandani; Rondhianto Rondhianto (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2025)
Several studies indicate a significant increase in diabetes and its complications in agricultural regions. Jember is an agricultural area with a high prevalence of diabetes and a heightened risk of Diabetic Foot Ulcer (DFU). Reducing aggressive risk factors involves a self-efficacy theory based program. This intervention aimed to evaluate the program's effectiveness on foot care behaviors, self-efficacy in self-care foot management, and the risk of DFU occurrence. The study spanned over six months, consisting of three stages: program introduction, health education delivery, and program evaluation. It employed a Pre-Experimental Design with a Group Pretest-Posttest approach. Sample selection was done using simple random sampling, resulting in a sample of 28 research participants. The statistical test used was the Wilcoxon Test. The study's results showed significance values for all three variables < 0.001, signifying the influence of the intervention. The risk of diabetic foot ulcers had a negative rank, indicating a decrease in the risk of DFU after the intervention, with an average reduction value of 13.00. Foot Self-Care Behavior showed a positive rank of 14.50, signifying an improvement in Foot Self-Care Behavior following the intervention. Foot Care Confidence displayed a positive rank, indicating an increase in Foot Care Confidence after the intervention, with an average improvement of 14.50. Consequently, nurses can implement a self-efficacy-based foot care education program to reduce the risk of diabetic ulcers by enhancing self-care behaviors and self-efficacy in independent foot care.